Effect of Adding Lactic Acid Bacteria to Maize Silage on Nutritive Guality, Fermentation Properties and in Vitro Digestibility - Nihat Denek; Sadık Serkan Aydın (Journal of Agricultural Sciences)
This study aimed to determine the effects of adding lactic acid bacteria to maize silage on the nutritional quality, fermentation properties, and its in vitro organic matter digestion (IVOMD). Pre-fermented juices (PFJ) prepared from different water-soluble carbohydrate (WSC) sources at the rate of 5% and commercial homofermentative and heterofermentative lactic acid bacteria (LAB) were added to silages. Groups were designed as (I) control, (II) Glucose-PFJ, (III) Fructose-PFJ, (IV) Sucrose-PFJ, (V) Molasses-PFJ, (VI) Homofermentative LAB (HoLAB) and (VII) Heterofermentative LAB (HetLAB). Lactic acid bacteria (LAB) count, lactic acid (LA), acetic acid (AA), LA/AA ratio, pH and yeast values of the natural fermented lactic acid bacteria liquids prepared by adding 5% of different easily soluble carbohydrate sources to meadow grass showed significant variations. The differences among the groups in the crude ash (CA), acid detergent fiber (ADF), IVOMD and methane (CH4) values of the silage groups prepared by adding PFJ were also found to be statistically significant. The differences in the fermentation characteristics of the silages (pH, ammonia-nitrogen (NH3-N), LA, AA, LA/AA, CO2, and total yeast mold after aerobic stability) were statistically significant too. When all parameters were examined, it was concluded that the addition of PFJ, which is prepared by adding 5% fructose to the meadow grass plant, to the maize silage has positive effects on IVOMD, ME, CH4, LA and yeast-mold and can be used instead of commercial inoculants.